Using the SuccessNavigator® Assessment to Assess Change Over Time: A Longitudinal Measurement Invariance Study. Issue 1 (26th July 2018) - Rikoon, Samuel H.; Midkiff, Brooke
Abstract: The assumption of longitudinal measurement invariance underlies the interpretation of changes in assessment scale score levels over time. This study was conducted to examine the longitudinal measurement invariance of the SuccessNavigator® assessment (SN) in a sample of 407 first‐year undergraduate students. SN is a psychosocial skills assessment targeting 4 broad domains (academic skills, commitment, self‐management, and social support). Each domain comprises 2 or 3 subskills (10 subskills total). Of the 10 subskills, 8 were found to demonstrate a sufficient level of both metric and scalar longitudinal measurement invariance, supporting their application in longitudinal studies. Implications of these findings are discussed, as are important avenues for future research to examine both the methodological and practical consequences of noninvariance in the 2 cases where it was observed. Abstract : Report Number: ETS RR–18‐29